Neck Circumference is an Effective Supplement for Nonalcoholic Fatty Liver Disease Screening in a Community-Based Population - Chaohui Jian; Yiting Xu; Xiaojing Ma; Yun Shen; Yufei Wang; Yuqian Bao (International Journal of Endocrinology)
Background. Accumulating evidence has shown that neck circumference (NC) is associated with obesity-related metabolic abnormalities. Nonalcoholic fatty liver disease (NAFLD) is regarded as a liver manifestation of metabolic syndrome. This study aimed to investigate the relationship between NC and liver fat content (LFC) and NAFLD. Methods. A total of 1698 subjects (577 men and 1121 women) from the Shanghai community were enrolled. All the subjects underwent NC measurement and biochemical measurements. LFC was calculated using the parameters from abdominal ultrasound images. Elevated NC was defined as NC ≥38.5 cm in men and NC ≥34.5 cm in women. Results. Subjects with NAFLD based on the LFC measurement had higher values of NC, liver enzyme profiles, homoeostasis model assessment-insulin resistance index, and LFC than those without NAFLD (all P<0.05), irrespective of sex. NC showed an upward trend with the increase of LFC in both men and women (both P<0.05). An elevated NC could identify 55.22% of men and 50.29% of women with NAFLD based on quantitative ultrasonography. The positive correlation between NC and LFC remained significant even after adjustment for central obesity (both P<0.05). After adjusting for confounding factors, the risk of NAFLD in subjects with an elevated NC was 1.52-fold higher in men (P=0.036) and 2.31-fold higher in women (P<0.001). Conclusions. There was a significant and positive correlation between NC and LFC. The risk of NAFLD increased significantly in subjects with an elevated NC.